Drying of cumaru seeds: influence on the germination and vigor - Varela, Vania Palmeira (2014)
This study was undertaken to evaluate the effect of drying on seed germination and seedling vigor for Cumaru (Dipteryx odorata (Aubi.) Willd.) at 40ºC for different periods. Daily counts were made of the number of germinated seedlings. At the end of the experiment the following parameters were evaluated: length of root and aerial portion, dry weight of root system and aerial portion. There was no correlation between seed moisture content and germination, nor between seed moisture and seedlings dry weight. A correlation was found, however, between rate of seedling emergence and percent germination.